Islamic Republic of Mauritania : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
The report describes the participatory process and its impact, and analyzes its shortcomings. Mauritania's progress report provides a candid review and analysis of the implementation of the Poverty Reduction Strategy Paper (PRSP). Becasue poverty remains primarily a rural phenomenon in Mauritania, more emphasis should have been placed on growth in the rural areas. Numerous actions have been taken in the context of the implementation of the ongoing reform of the semi-urban and rural water sector. Actions in the area of urban development are also welcomed.